Analytically continued fock space multi-reference coupled-cluster theory: application to the shape resonance - Pal, Sourav; Sajeev, Y.; Vaval, Nayana (Chemical Physics, 2006)
The Fock space multi-reference coupled-cluster (FSMRCC) method is used for the study of the shape resonance energy and width in an electron-atom/molecule collision. The procedure is based upon combining a complex absorbing potential (CAP) with FSMRCC theory. Accurate resonance parameters are obtained by solving a small non-Hermitian eigen-value problem. We study the shape resonances in e(-)-C2H4 and e(-)-Mg. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: complex absorbing potential; correlated independent particle potential; Fock space multi-reference coupled-cluster theory; shape resonance

Constrained variational response to Fock-space multi-reference coupled-cluster theory: Some pilot applications - Manohar, Prashant Uday; Vaval, Nayana; Pal, Sourav (Journal of Molecular Structure-Theochem, 2006)
Fock space (FS) multi-reference (MR) coupled-cluster (CC) has been established to be state-of-the-art method for energies of open-shell radicals, ionized, electron attached states and excited states. Due to the multi-root nature of the method, the linear response of MRCC, however, is non-trivial. Constrained variation approach (CVA) makes it plausible to calculate response of the MRCC method efficiently. However, the approach is used for only one root of the problem at a time. In the present article, we make first implementation of the approach and present test results of dipole moments of small radicals. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: constrained variation; coupled-cluster; Dipole moment; Multi-reference; response

Ab initio lifetimes in the interatomic coulombic decay of neon clusters computed with propagators - Vaval, Nayana; Cederbaum, Lorenz S. (Journal of Chemical Physics, 2007)

Shape resonance in electron molecule scattering using coupled cluster method - Pal, Sourav; Vaval, Nayana; Sajeev, Y. (Indian Journal of Physics and Proceedings of the Indian Association for the Cultivation of Science, 2007)
The Fock space multi-reference coupled-cluster (FSMRCC) method along with the complex absorbing potential (CAP) is used for the study of the shape resonance energy and width in an electron molecule collision. We study the shape resonances in e(-) -H2CO and e(-) -CO.
Keywords: electron-molecule scattering; multi-reference coupled-cluster

First- and second-order electrical properties computed at the FSMRCCSD level for excited states of closed-shell molecules using the constrained-variational approach - Bag, Arijit; Manohar, Prashant Uday; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2009)
Fock space multireference coupled-cluster (FSMRCC) method emerged as an efficient tool to describe the electronic structure of nearly degenerate cases. Development of linear response has been one of the challenging problems in FSMRCC due to the multiple-root nature of the effective Hamiltonian. A response from any of the roots would span the space for getting the properties. Hence, all roots perturbed by the external field would proliferate the excited states. We recently developed the FSMRCC method for the efficient evaluation of analytic response properties using a constrained variation approach. In this paper, we present analytic dipole moments and polarizabilities of H2O, O-3, and CH+ molecules in low-lying excited states along with brief discussion of singlet triplet decoupling of (1,1) sector of FSMRCC resulting from spin adaptation. (C) 2009 American Institute of Physics. [DOI: 10.1063/1.3167796]

Magnetizability of doublet radicals using fock space multi-reference coupled cluster method - Ravichandran, Lalitha; Vaval, Nayana; Pal, Sourav (International Journal of Quantum Chemistry, 2009)
In this article, we report the first implementation of the recently developed Fock space multi reference Coupled cluster (FSMRCC) response approach for magnetizabilities. The FSM-RCC treats dynamic and static correlation in a very extensive manner. We report pilot application of the diarnagnetizability of NO, NO2, OH, and BH2 radicals. We also report preliminary applications of the paramagnetic magnetizability of the NO radical. Standard atom-centered Gaussian basis functions have been used, and this allowed US to Study the gauge dependence of the magnetizabilities. (C) 2009 Wiley Periodicals, Inc. Int J Quantum Chem 109: 2191-2198, 2009
Keywords: Fock space; magnetizability; multireference

Chemical shielding of closed-shell molecules using extended coupled-cluster theory - Ravichandran, Lalitha; Joshi, Sayali; Vaval, Nayana (International Conference on Recent Advances in Spectroscopy - Theoretical, Astrophysical and Experimental Perspectives, 2010)
In this paper we report calculation of the nuclear magnetic shielding constant using extended coupled cluster response approach. We present the results for the HF, BH, CO and N(2) molecules. These results show importance of correlation corrections for the shielding constant.
International Conference on Recent Advances in Spectroscopy - Theoretical, Astrophysical and Experimental Perspectives, Indian Inst Astrophys, Kodaikanal Observatory, Bangalore, INDIA, JAN 28-31, 2009

On some aspects of fock-space multi-reference coupled-cluster singles and doubles energies and optical properties - Manohar, Prashant Uday; Shamasundar, K. R.; Bag, Arijit; Vaval, Nayana; Pal, Sourav (Recent progress in coupled cluster methods: theory and applications, 2010)

Effect of triples to dipole moments in fock-space multireference coupled cluster method - Ravichandran, Lalitha; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2011)
In this paper, we present the new implementation of partial triples for the dipole moment of doublet radicals in Lagrangian formulation of Fock-space multireference coupled cluster (A-FSMRCC) response method. We have implemented a specific scheme of noniterative triples, in addition to singles and doubles schemes, which accounts for the effects appearing at least at the third order in dipole moments. The method is applied to the ground states of OH, OOH, HCOO, CN, CH, and PO radicals.

Constrained variational approach for energy derivatives in Intermediate hamiltonian fock-space coupled-cluster theory - Ghosh, Aryya; Gupta, Jitendra; Pal, Sourav; Vaval, Nayana (Chemical Physics, 2012)
Fock-space multi-reference coupled cluster theory is an efficient method for electronic structure of nearly degenerate cases. However, it suffers from the intruder state problem for large model space. The intermediate Hamiltonian formulation eliminates intruder state problem and helps in the convergence of equations. In this paper we have implemented intermediate Hamiltonian approach in Fock-space coupled cluster method for the response properties. We test our method for the dipole moments of doublet radicals. We report dipole moments of CN, SF and NS radicals. (C) 2011 Elsevier B. V. All rights reserved.
Keywords: Constrained variational approach; Fock-space multi-reference coupled cluster; Intermediate Hamiltonian theory; Response approach

Equation-of-motion coupled-cluster method for the study of shape resonance - Ghosh, Aryya; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2012)
The equation-of-motion coupled-cluster method (EOM-CC) is applied for the first time to calculate the energy and width of a shape resonance in an electron-molecule scattering. The procedure is based on inclusion of complex absorbing potential with EOM-CC theory. We have applied this method to investigate the shape resonance in e(-)N(2), e(-)CO, and e(-)C(2)H(2). (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4729464]

Extended coupled cluster for Raman and infrared spectra of small molecules - Joshi, Sayali P.; Dutta, Achintya Kumar; Pal, Sourav; Vaval, Nayana (Chemical Physics, 2012)
In this paper we study the harmonic vibrational frequencies, infrared (IR) intensities, Raman intensities and depolarization ratio using extended coupled cluster method. Raman and IR intensities are mixed derivatives of energy with respect to the electric field and geometric perturbation whereas vibrational frequencies are derivatives of energy with respect to geometry. We use semi-numerical approach to obtain these derivatives. We have studied the effect of electron correlation and basis set for the above properties. We compare our results with non-variational coupled cluster and experimental values, wherever available. We have studied HF, BH, CH+, CO and H2CO molecules in different basis sets. For HF molecule, benchmarking is done with full CI values and basis set convergence is studied for this molecule. Effect of triples is studied for all the molecules. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Extended coupled cluster; IR and Raman spectroscopy; Mixed derivatives

Fock-space multi-reference coupled-cluster response with the effect of triples on dipole moment of ClO and SF radicals - Ravichandran, Lalitha; Bhattacharya, Debarati; Vaval, Nayana; Pal, Sourav (Journal of Chemical Sciences, 2012)

NOx catalyzed pathway of stratospheric ozone depletion: a coupled cluster investigation - Dutta, Achintya Kumar; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2012)
We report a theoretical investigation on the NOx catalyzed pathways of stratospheric ozone depletion using highly accurate coupled cluster methods. These catalytic reactions represent a great challenge to state-of-the-art ab initio methods, while their mechanisms remain unclear to both experimentalists and theoreticians. In this work, we have used the so-called ``gold standard of quantum chemistry,'' the CCSD(T) method, to identify the saddle points on NOx-based reaction pathways of ozone hole formation. Energies of the saddle points are calculated using the multireference variants of coupled cluster methods. The calculated activation energies and rate constants show good agreement with available experimental results. Tropospheric precursors to stratospheric NOx radicals have been identified, and their potential importance in stratospheric chemistry has been discussed. Our calculations resolve previous conflicts between ab initio and experimental results for a trans nitro peroxide intermediate, in the NOx catalyzed pathway of ozone depletion.

CAP/EOM-CCSD method for the study of potential curves of resonant states - Ghosh, Aryya; Karne, Anagha S.; Pal, Sourav; Vaval, Nayana (Physical Chemistry Chemical Physics, 2013)
The equation-of-motion coupled-cluster (EOM-CC) method along with the complex absorbing potential (CAP) is used for the study of resonance in e(-)-N-2 and e(-)-CO. Resonance position and width are studied as a function of bond length. We report the potential curves (PC) of the resonance states.

Electronic transition dipole moments and dipole oscillator strengths within fock-space multi-reference coupled cluster framework: an efficient and novel approach - Bhattacharya, Debarati; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2013)
Within the Fock-space multi-reference coupled cluster framework, we have evaluated the electronic transition dipole moments, which determine absorption intensities. These depend on matrix elements between two different wave functions (e. g., ground state to the excited state). We present two different ways, to calculate these transition moments. In the first method, we construct the ground and excited state wave functions with the normal exponential ansatz of Fock-space coupled cluster method and then calculate the relevant off-diagonal matrix elements. In the second approach, we linearize the exponential form of the wave operator which will generate the left vector, by use of Lagrangian formulation. The right vector is obtained from the exponential ansatz. In order to relate the transition moments to oscillator strengths, excitation energies need to be evaluated. The excitation energies are obtained from the Fock-space multi-reference framework. The transition dipole moments of the ground to a few excited states, together with the oscillator strengths of a few molecules, are presented. (C) 2013 American Institute of Physics. [http://dx.doi.org/10.1063/1.4793277]

Extended coupled cluster through nth perturbation order for molecular response properties: a comparative study - Gupta, Jitendra; Manohar, Prashant Uday; Ghosh, Aryya; Vaval, Nayana; Pal, Sourav (Chemical Physics, 2013)
In this paper, we have presented and analyzed the extended coupled cluster (ECC) energy functional, truncated up to nth perturbation order in which expansion is limit to operators of the single and double excitations. The expression for the first order energy derivatives based on the above truncation schemes has been derived and numerically analyzed. We have done a comparative study for dipole moment in various perturbative ECC (n) methods (2 <= n <= 5) for three systems (HF, H2O and BH) at equilibrium geometry. We have particularly studied two variants of ECC (4) and ECC (5*) method for stretched geometry. We have analyzed the contribution of important terms present in ECC functional based on perturbative argument. We have compared our results with standard coupled cluster (CCSD) as well as cubic truncated ECC and also benchmarked with the full CI results wherever available. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Dipole moment; Energy functional; Extended coupled cluster

Fock space multireference coupled cluster theory: study of shape resonance - Bhattacharya, Sumantra; Vaval, Nayana; Pal, Sourav (International Journal of Quantum Chemistry, 2013)
The complex absorbing potential along with correlated independent particle potential (CIP) Fock space multireference coupled cluster method is used for the study of resonances. We have studied shape resonance of e(-) - F-2, e(-) - N2O and e(-) -CO molecules. In particular, we have studied e(-) - F-2 scattering at different bond lengths to know whether F-2(-) is bound at the equilibrium bond length of F-2. (C) 2013 Wiley Periodicals, Inc.
Keywords: correlated independent particle potential; Fock-space multireference coupled cluster theory; shape resonance

Interatomic coulombic decay in (HF)n,(n=2-3) clusters using CAP/EOM-CCSD method - Ghosh, Aryya; Pal, Sourav; Vaval, Nayana (Molecular Physics, 2013)
The equation-of-motion coupled-cluster method along with the complex absorbing potential has been applied to study the interatomic Coulombic decay mechanism in hydrogen-bonded clusters. We have applied this method to calculate the lifetime of the F 2s inner-valence ionised state of (HF)(n) (n = 2-3) clusters. The lifetime is found to be very short and decreases substantially with increasing the number of HF monomer.
Keywords: complex absorbing potential (CAP); equation-of-motion coupled-cluster (EOM-CC); HF clusters; interatomic Coulombic decay (ICD)

Lagrange multiplier approach for excited state properties through intermediate hamiltonian formulation of fock space multireference coupled-cluster theory - Gupta, Jitendra; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2013)
In this paper, we present a formulation based on Lagrange multiplier approach for efficient evaluation of excited state energy derivatives in Fock space coupled cluster theory within the intermediate Hamiltonian framework. The formulation is applied to derive the explicit generic expressions up to second order energy derivatives for [1, 1] sector of Fock space with singles and doubles approximation. Its advantage, efficiency, and interconnection in comparison to the Lagrange multiplier approach in traditional formulation of Fock space, which is built on the concept of Bloch equation based effective Hamiltonian, has been discussed. Computational strategy for their implementation has also been discussed in some detail. (C) 2013 AIP Publishing LLC.

Multipole moments using extended coupled cluster method - Joshi, Sayali P.; Vaval, Nayana (Chemical Physics Letters, 2013)
Using analytic extended coupled cluster (ECC) response approach quadrupole moments, dipole-quadrupole polarizabilities and dipole polarizabilities are studied. In the current implementation of the functional we have included all the double linked terms within (CCSD) approximation. These terms will be important for the accurate description of properties at the stretched geometries. We report the properties for carbon monoxide and hydrogen fluoride molecules, as a function of bond distance and compare our results for carbon monoxide with the full Cl results. We have also reported the properties of methane, tetrafluoromethane, acetylene, difluoroacetylene, water and ammonia. (C) 2013 Elsevier B.V. All rights reserved.

Performance of the EOMIP-CCSD(2) method for determining the structure and properties of doublet radicals: a benchmark investigation - Dutta, Achintya Kumar; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2013)
We present a benchmark study on the performance of the EOMIP-CCSD(2) method for computation of structure and properties of doublet radicals. The EOMIP-CCSD(2) method is a second-order approximation to the standard EOMIP-CCSD method. By retaining the black box nature of the standard EOMIP-CCSD method and adding favorable N-5 scaling, the EOMIP-CCSD(2) method can become the method of choice for predicting the structure and spectroscopic properties of large doublet radicals. The EOMIP-CCSD(2) method overcomes the typical problems associated with the standard single reference ab initio treatment of doublet radicals. We compare our results for geometries and harmonic vibrational frequencies with those obtained using the standard EOMIP-CCSD method, as well as unrestricted Hartree-Fock (UHF)- and restricted open-shell Hartree-Fock (ROHF)-based single-reference coupled-cluster and second order many-body perturbation theory (MBPT(2)) methods. The effect of the basis set on the quality of the results has been studied using a hierarchy of Dunning's correlation-consistent aug-cc-pVXZ (X = D, T, Q) basis sets. Numerical results show that the EOMIP-CCSD(2) method, despite its N-5 scaling, gives better agreement with experimental results, compared to the UHF- and ROHF-based MBPT(2), as well as the single-reference coupled-cluster methods.

Polarizability of few electron quantum dots: extended coupled-cluster response approach - Heidari, Ideh; Vaval, Nayana; Pal, Sourav; Kanhere, Dilip G. (Chemical Physics Letters, 2013)
The dipole polarizability is studied for few electron quantum dots using extended coupled cluster linear response method (ECCLR). The polarizability of pure parabolic quantum dots depends only on the number of electrons and the parabolic confinement strength. We added impurity in a GAUSSIAN form to the external parabolic potential and used ECCLR to calculate polarizability. To examine the effect of external potential, we changed the parabolic confinement to square-well and repeated all calculations. We mainly looked at eigenvalue spectrum and charge density specially when the system shifts towards lower density regions. (C) 2012 Elsevier B. V. All rights reserved.

Study of interatomic coulombic decay of Ne(H2O)(n) (n=1,3) clusters using equation-of-motion coupled-cluster method - Ghosh, Aryya; Pal, Sourav; Vaval, Nayana (Journal of Chemical Physics, 2013)
Interatomic Coulombic decay (ICD) is an efficient and ultrafast radiationless decay mechanism which can be initiated by removal of an electron from the inner-valence shell of an atom or molecule. Generally, the ICD mechanism is prevailed in weakly bound clusters. A very promising approach, known as CAP/EOM-CC, consists of the combination of complex absorbing potential (CAP) with the equation-of-motion coupled-cluster (EOM-CC) method, is applied for the first time to study the nature of the ICD mechanism. We have applied this technique to determine the lifetime of an auto-ionized, inner-valence excited state of the NeH2O, Ne(H2O)(2), and Ne(H2O)(3) systems. The lifetime is found to be very short and decreases significantly with the number of neighboring water molecules. (C) 2013 AIP Publishing LLC.

Complex absorbing potential based equation-of-motion coupled cluster method for the potential energy curve of CO2- anion - Ghosh, Aryya; Vaval, Nayana; Pal, Sourav; Bartlett, Rodney J. (Journal of Chemical Physics, 2014)
The equation-of-motion coupled cluster method employing the complex absorbing potential has been used to investigate the low energy electron scattering by CO2. We have studied the potential energy curve for the (2)Pi(u) resonance states of CO2- upon bending as well as symmetric and asymmetric stretching of the molecule. Specifically, we have stretched the C-O bond length from 1.1 angstrom to 1.5 angstrom and the bending angles are changed between 180 degrees and 132 degrees. Upon bending, the low energy (2)Pi(u) resonance state is split into two components, i.e., (2)A(1), B-2(1) due to the Renner-Teller effect, which behave differently as the molecule is bent. (c) 2014 AIP Publishing LLC.

Electronic transition dipole moment: a semi-biorthogonal approach within valence universal coupled cluster framework - Bhattacharya, Debarati; Vaval, Nayana; Pal, Sourav (International Journal of Quantum Chemistry, 2014)
Electronic dipole strengths (square of transition moments) and oscillator strengths are evaluated for various transitions, arising from the ground state to a few valence excited states. Parallel to two other methods of calculating the dipole strength within the Fock-space multireference coupled cluster framework, a new semi-biorthogonal approach is formulated and implemented in this article. This semi-biorthogonal approach can evaluate dipole strengths at a lower computational effort than the biorthogonal approach without compromising on the accuracy. This new method is compared and tested against the previously developed expectation value and biorthogonal approach for various molecular transitions. (C) 2014 Wiley Periodicals, Inc.
Keywords: electronic transition dipole; Fock-space; oscillator strength; semi-biorthogonal expectation value

Extended coupled cluster method for potential energy surface: a decoupled approach - Joshi, Sayali P.; Vaval, Nayana (Chemical Physics Letters, 2014)
Extended coupled cluster (ECC) method has been implemented extensively for the calculation of molecular properties. In this Letter we report the potential energy surface (PES) study using coupled and a decoupled approximation of ECC. HF, N-2 and C-2 are studied as test systems. N-2 and C-2 being doubly and triply bonded, are considered to be interesting systems for PES study. We compare our results with full CI (FCI) results wherever available. Decoupled approach within ECC framework shows good convergence for all the molecules. (C) 2014 Elsevier B.V. All rights reserved.

Geometry-dependent lifetime of Interatomic coulombic decay using equation-of-motion coupled cluster method - Ghosh, Aryya; Vaval, Nayana (Journal of Chemical Physics, 2014)
Electronically excited atom or molecule in an environment can relax via transferring its excess energy to the neighboring atoms or molecules. The process is called Interatomic or Intermolecular coulombic decay (ICD). The ICD is a fast decay process in environment. Generally, the ICD mechanism predominates in weakly bound clusters. In this paper, we have applied the complex absorbing potential approach/equation-of-motion coupled cluster (CAP/EOMCCSD) method which is a combination of CAP and EOMCC approach to study the lifetime of ICD at various geometries of the molecules. We have applied this method to calculate the lifetime of ICD in Ne-X; X = Ne, Mg, Ar, systems. We compare our results with other theoretical and experimental results available in literature. (C) 2014 AIP Publishing LLC.

Ground state of naphthyl cation: singlet or triplet? - Dutta, Achintya Kumar; Manohar, Prashant Uday; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2014)
We present a benchmark theoretical investigation on the electronic structure and singlet- triplet(ST) gap of 1- and 2-naphthyl cations using the CCSD(T) method. Our calculations reveal that the ground states of both the naphthyl cations are singlet, contrary to the results obtained by DFT/B3LYP calculations reported in previous theoretical studies. However, the triplet states obtained in the two structural isomers of naphthyl cation are completely different. The triplet state in 1-naphthyl cation is (pi,sigma) type, whereas in 2-naphthyl cation it is (pi,sigma) type, The S-T gaps in naphthyl cations and the relative stability ordering of the singlet and the triplet states are highly sensitive to the basis set quality as well as level of correlation, and demand for inclusion of perturbative triples in the coupled-cluster ansatz. (c) 2014 AIP Publishing LLC.

Intermediate hamiltonian fock space multireference coupled cluster approach to core excitation spectra - Dutta, Achintya Kumar; Gupta, Jitendra; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2014)
The Fock space multireference coupled cluster (FSMRCC) method provides an efficient approach for the direct calculation of excitation energies. In intermediate Hamiltonian (IH-FSMRCC) formulation, the method is free from intruder state problems and associated convergence difficulties, even with a large model space. In this paper, we demonstrate that the IH-FSMRCC method with suitably chosen model space can be used for the accurate description of core excitation spectra of molecules, and our results are in excellent agreement with the experimental values. We have investigated the effect of choice of model space on the computed results. Unlike the equation-of-motion (EOM)-based method, the IH-FSMRCC does not require any special technique for convergence and in singles and doubles approximation gives a performance comparable to that of the standard EOMEE-CCSD method, even better in some of the cases.

Partitioned EOMEA-MBPT(2): an efficient N-5 scaling method for calculation of electron affinities - Dutta, Achintya Kumar; Gupta, Jitendra; Pathak, Himadri; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2014)
We present an N-5 scaling modification to the standard EOMEA-CCSD method, based on the matrix partitioning technique and perturbative approximations. The method has lower computational scaling and smaller storage requirements than the standard EOMEA-CCSD method and, therefore, can be used to calculate electron affinities of large molecules and clusters. The performance and capabilities of the new method have been benchmarked with the standard EOMEA-CCSD method, for a test set of 20 small molecules, and the average absolute deviation is only 0.03 eV. The method is further used to investigate electron affinities of DNA and RNA nucleobases, and the results are in excellent agreement with the experimental values.

Relativistic equation-of-motion coupled-cluster method: application to closed-shell atomic systems - Pathak, Himadri; Sahoo, B. K.; Das, B. P.; Vaval, Nayana; Pal, Sourav (Physical Review Applied, 2014)
We report our successful implementation of the relativistic equation-of-motion coupled-cluster (EOMCC) method. This method is employed to compute the principal ionization potentials (IPs) of closed-shell rare-gas atoms, He-like ions, Be-like ions, along with Na+, Al+, K+, Be, andMg. Four-component Dirac spinors are used in the calculations, and the one-and two-electron integrals are evaluated using the Dirac-Coulomb Hamiltonian. Our results are in excellent agreement with available measurements, which are taken from the National Institute of Science and Technology database. The accuracies of the calculations are estimated to be within one half of a percent for He-like and Be-like ions and 1% for the heavier systems. We also present results using the second-order many-body perturbation theory and random-phase approximation in the EOMCC framework. These results are compared with those of EOMCC at the level of single and double excitations in order to assess the role of the electron correlation effects in the intermediate schemes considered in our calculations.

Relativistic equation-of-motion coupled-cluster method for the double-ionization potentials of closed-shell atoms - Pathak, Himadri; Ghosh, Aryya; Sahoo, B. K.; Das, B. P.; Vaval, Nayana; Pal, Sourav (Physical Review A, 2014)

Relativistic equation-of-motion coupled-cluster method for the ionization problem: application to molecules - Pathak, Himadri; Sasmal, Sudip; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Physical Review A, 2014)
We report the implementation of the four-component spinor relativistic equation-of-motion (EOM) coupled-cluster method within the single- and double-excitation approximation to calculate the ionization potential of molecules. We have applied this method to calculate vertical ionization potentials of the molecules XH (X = F, Cl, Br, I) along with Cl-2 and Br-2 in their closed-shell configuration. We have also presented intermediate results using the second-order many-body perturbation-theory level in the EOM framework to understand the role of electron correlation. All the calculated values are compared with the available experimental results. Our results are found to be in good agreement with sophisticated experiments, and relative deviation of less than 1% is achieved for all the considered systems.

Structure, stability, and properties of the trans peroxo nitrate radical: the importance of nondynamic correlation - Dutta, Achintya Kumar; Dar, Manzoor; Vaval, Nayana; Pal, Sourav (Journal of Physical Chemistry A, 2014)
We report a comparative single-reference and multireference coupled-cluster investigation on the structure, potential energy surface, and IR spectroscopic properties of the trans peroxo nitrate radical, one of the key intermediates in stratospheric NOx chemistry. The previous single-reference ab initio studies predicted an unbound structure for the trans peroxo nitrate radical. However, our Fock space multireference coupled-cluster calculation confirms a bound structure for the trans peroxo nitrate radical, in accordance with the experimental results reported earlier. Further, the analysis of the potential energy surface in FSMRCC method indicates a well-behaved minima, contrary to the shallow minima predicted by the single-reference coupled-cluster method. The harmonic force field analysis, of various possible isomers of peroxo nitrate also reveals that only the trans structure leads to the experimentally observed IR peak at 1840 cm(-1). The present study highlights the critical importance of nondynamic correlation in predicting the structure and properties of high-energy stratospheric NOx radicals.

Calculation of P,T-odd interaction constant of PbF using Z-vector method in the relativistic coupled-cluster framework - Sasmal, Sudip; Pathak, Himadri; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2015)
The effective electric field experienced by the unpaired electron in the ground state of PbF, which is a potential candidate in the search of electron electric dipole moment due to some special characteristics, is calculated using Z-vector method in the coupled cluster single-and double-excitation approximation with four component Dirac spinor. This is an important quantity to set the upper bound limit of the electron electric dipole moment. Further, we have calculated molecular dipole moment and parallel magnetic hyperfine structure constant (A(parallel to)) of Pb-207 in PbF to test the accuracy of the wavefunction obtained in the Z-vector method. The outcome of our calculations clearly suggests that the core electrons have significant contribution to the ``atom in compound'' properties. (C) 2015 AIP Publishing LLC.

Electron attachment to DNA and RNA nucleobases: an EOMCC investigation - Dutta, Achintya Kumar; Sengupta, Turbasu; Vaval, Nayana; Pal, Sourav (International Journal of Quantum Chemistry, 2015)
We report a benchmark theoretical investigation of both vertical and adiabatic electron affinities of DNA and RNA nucleobases: adenine, guanine, cytosine, thymine, and uracil using equation of motion coupled cluster method. The vertical electron affinity (VEA) values of the first five states of the DNA and RNA nucleobases are computed. It is observed that the first electron attached state is energetically accessible in gas phase. Furthermore, an analysis of the natural orbitals exhibits that the first electron attached states of uracil and thymine are valence-bound in nature and undergo significant structural changes on attachment of an extra electron, which reflects in the deviation of the adiabatic electron affinity (AEA) than that of the vertical ones. Conversely, the first electron attached states of cytosine, adenine, and guanine are in the category of dipole-bound anions. Their structure, by and large, remain unaffected on attachment of an extra electron, which is evident from the observed small difference between the AEA and VEA values. VEA and AEA values of all the DNA and RNA nucleobases are found to be negative, which implies that the first electron attached states are not stable rather quasi bound. The results of all previous theoretical calculations are out of track and shows large deviation with respect to the experimentally measured values, whereas, our results are found to be in good agreement. Therefore, our computed values can be used as a reliable standard to calibrate new theoretical methods. (c) 2015 Wiley Periodicals, Inc.
Keywords: DNA-RNA bases; electron affinity; EOMCC

EOMIP-CCSD(2)*: an efficient method for the calculation of ionization potentials - Dutta, Achintya Kumar; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2015)
A new approximation within the domain of EOMIP-CC method is proposed. The proposed scheme is based on the perturbative truncation of the similarity transformed effective Hamiltonian matrix. We call it the EOMIP-CCSD(2)* method, which scales as noniterative N-6 and its storage requirement is very less, compared to the conventional EOMIP-CCSD method. The existing EOMIP-CCSD(2) method has a tendency to overestimate the ionization potential (IP) values. On the other hand, our new strategy corrects for the problem of such an overestimation, which is evident from the excellent agreement achieved with the experimental values. Furthermore, not only the ionization potential but also geometry and IR frequencies of problematic double radicals are estimated correctly, and the results are comparable to the CCSD(T) method, obviously at lesser computational cost. The EOMIP-CCSD(2)* method works even for the core ionization and satellite IP, where the earlier EOMIP-CCSD(2) approximation dramatically fails.

Implementation of the Z-vector method in the relativistic-coupled-cluster framework to calculate first-order energy derivatives: Application to the SrF molecule - Sasmal, Sudip; Pathak, Himadri; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Physical Review A, 2015)
The molecular dipole moment and magnetic hyperfine-structure constant demand an accurate wave function far from the nucleus and in the near nuclear region, respectively. We, therefore, employ the so-called Z-vector method in the domain of relativistic-coupled-cluster theory to calculate the first-order property of molecular systems in their open-shell ground-state configuration. The implemented method is applied to calculate the molecular dipole moment and parallel component of the magnetic hyperfine-structure constant of the SrF molecule. The results of our calculation are compared with the experimental and other available theoretically calculated values. We are successful in achieving good accordance with the experimental results. The result of our calculation of the molecular dipole moment is in the accuracy of similar to 0.5%, which is clearly an improvement over the previous calculation based on the expectation value method in the four-component coupled-cluster framework [V. S. Prasannaa et al., Phys. Rev. A 90, 052507 (2014)]. Thus, it can be inferred that the Z-vector method can provide an accurate wave function in both the near and far nuclear region, which is evident from our calculated results.

Lifetime of inner-shell hole states of Ar (2p) and Kr (3d) using equation-of-motion coupled cluster method - Ghosh, Aryya; Pal, Sourav; Vaval, Nayana (Journal of Chemical Physics, 2015)

New scheme for perturbative triples correction to (0,1) sector of Fock space multi-reference coupled cluster method: Theory, implementation, and examples - Dutta, Achintya Kumar; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2015)
We propose a new elegant strategy to implement third order triples correction in the light of many-body perturbation theory to the Fock space multi-reference coupled cluster method for the ionization problem. The computational scaling as well as the storage requirement is of key concerns in any many-body calculations. Our proposed approach scales as N-6 does not require the storage of triples amplitudes and gives superior agreement over all the previous attempts made. This approach is capable of calculating multiple roots in a single calculation in contrast to the inclusion of perturbative triples in the equation of motion variant of the coupled cluster theory, where each root needs to be computed in a state-specific way and requires both the left and right state vectors together. The performance of the newly implemented scheme is tested by applying to methylene, boron nitride (B2N) anion, nitrogen, water, carbon monoxide, acetylene, formaldehyde, and thymine monomer, a DNA base. (C) 2015 AIP Publishing LLC.

Partial triples excitation to the fock space multi-reference singles and doubles: dipole moment of doublet radicals - Ravichandran, Lalitha; Vaval, Nayana; Pal, Sourav (Proceedings of the International Conference of Computational Methods in Sciences and Engineering 2010 (ICCMSE-2010), 2015)
We present the partial triples effect on the dipole moment of doublet radicals in Lagrangian formulation of Fockspace multi-reference coupled cluster response method(A FSMRCC). This specific scheme uses non-iterative triples, in addition to singles and doubles excitations(A FSMRCCSD(T*)), which accounts for the effects appearing at least at the third order in dipole moment. This method is applied to the ground states of small radicals.
International Conference of Computational Methods in Sciences and Engineering (ICCMSE), Kos, GREECE, OCT 03-08, 2010
Keywords: Dipole moment; Multi-reference; Triples

Relativistic equation-of-motion coupled-cluster investigation of the trends of single and double ionization potentials in the He and Be isoelectronic systems - Pathak, Himadri; Sahoo, B. K.; Sengupta, Turbasu; Das, B. P.; Vaval, Nayana; Pal, Sourav (Journal of Physics B-Atomic Molecular and Optical Physics, 2015)
We employ a four-component spinor relativistic equation-of-motion coupled-cluster (EOMCC) method within the single-and double-excitation approximation to calculate the single ionization potentials (IPs) and double ionization potentials (DIPs) of the He and Be isoelectronic sequences up to Ne. The obtained results are compared with the available results from the National Institute of Standards and Technology (NIST) database to test the performance of the EOMCC method. We also present intermediate results at different levels of approximations in the EOMCC framework to gain insight of the effect of electron correlation. Furthermore, we investigate the dependence of the IPs and DIPs of these ions on the ionic charge and observe that these follow parabolic trends. Similarities between the trends of IPs and DIPs in both the classes of considered systems are categorically demonstrated.
Keywords: coupled-cluster method; double ionization potentials; equation-of-motion theory

Relativistic extended coupled cluster method for magnetic hyperfine structure constant - Sasmal, Sudip; Pathak, Himadri; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Physical Review A, 2015)

Systematic comparison of DFT and CCSD dipole moments, polarizabilities and hyperpolarizabilities (vol 635, pg 168, 2015) - Karne, Anagha S.; Vaval, Nayana; Pal, Sourav; Vasquez-Perez, Jose M.; Koester, Andreas M.; Calaminici, Patrizia (Chemical Physics Letters, 2015)

Systematic comparison of DFT and CCSD dipole moments, polarizabilities and hyperpolarizabilities - Karne, Anagha S.; Vaval, Nayana; Pal, Sourav; Vasquez-Perez, Jose M.; Koester, Andreas M.; Calaminici, Patrizia (Chemical Physics Letters, 2015)
A comparative study of dipole moments, polarizabilities and hyperpolarizabilities of 16 different molecules is performed employing two completely different theoretical approaches namely, density functional theory (DFT) and coupled cluster singles and doubles (CCSD). Both methods include electron correlation. The CCSD method is more accurate but highly expensive. DFT with auxiliary density allows non-iterative solutions which is computational advantage and useful for large molecules. Dipole moments and polarizability calculations from DFT are in very good agreement with CCSD calculations. However, negative hyperpolarizability values from DFT differ significantly from their CCSD counterparts, whereas positive hyperpolarizabilities show reasonable agreement between these methodologies. (C) 2015 Elsevier B.V. All rights reserved.

Calculation of hyperfine structure constants of small molecules using Z-vector method in the relativistic coupled-cluster framework - Sasmal, Sudip; Talukdar, Kaushik; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Journal of Chemical Sciences, 2016)
The Z-vector method in the relativistic coupled-cluster framework is employed to calculate the parallel and perpendicular components of the magnetic hyperfine structure constant of a few small alkaline earth hydrides (BeH, MgH, and CaH) and fluorides (MgF and CaF). We have compared our Z-vector results with the values calculated by the extended coupled-cluster (ECC) method reported in Phys. Rev. A 91 022512 (2015). All these results are compared with the available experimental values. The Z-vector results are found to be in better agreement with the experimental values than those of the ECC values.

Relativistic coupled-cluster study of RaF as a candidate for the parity- and time-reversal-violating interaction - Sasmal, Sudip; Pathak, Himadri; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Physical Review A, 2016)
We have employed both the Z-vector method and the expectation-value approach in the relativistic coupled-cluster framework to calculate the scalar-pseudoscalar (S-PS) P, T-odd interaction constant W-s and the effective electric field E-eff experienced by the unpaired electron in the ground electronic state of RaF. Further, the magnetic hyperfine structure constants of Ra-223 in RaF and Ra-223(+) are also calculated and compared with the experimental values wherever available to judge the extent of the accuracy obtained with the employed methods. The outcome of our study reveals that the Z-vector method is superior to the expectation-value approach in terms of accuracy obtained for the calculation of ground-state property. The Z-vector calculation shows that RaF has a high Eeff (52.5 GV/cm) and W-s (141.2 kHz), which makes it a potential candidate for the electric dipole moment of the electron (eEDM) experiment. An estimation of uncertainty associated with our final results is made, and it is found that it lies below 10%.

Relativistic equation-of-motion coupled-cluster method for the electron attachment problem - Pathak, Himadri; Sasmal, Sudip; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Computational and Theoretical Chemistry, 2016)
The article considers the successful implementation of relativistic equation-of-motion coupled cluster method for the electron attachment problem (EA-EOMCC) at the level of single- and double- excitation approximation. The implemented relativistic EA-EOMCC method is employed to calculate ionization potential values of alkali metal atoms (Li, Na, K, Rb, Cs, Fr) and the vertical electron affinity values of LiX (X = H, F, Cl, Br), NaY (Y = H, F, Cl) starting from their closed-shell configuration. Both four component and exact two-component calculations are done for all the opted systems. Further, we have shown the effect of spin-orbit interaction considering the atomic systems. The results of our atomic calculations are compared with the values from the NIST database and the results are found to be very accurate (<1%). (C) 2015 Elsevier B.V. All rights reserved.

Search for parity and time reversal violating effects in HgH: relativistic coupled-cluster study - Sasmal, Sudip; Pathak, Himadri; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2016)
The high effective electric field (E-eff) experienced by the unpaired electron in an atom or a molecule is one of the key ingredients in the success of electron electric dipole moment (eEDM) experiment and its precise calculation requires a very accurate theory. We, therefore, employed the Z-vector method in the relativistic coupled-cluster framework and found that HgH has a very large E-eff value (123.2 GV/cm) which makes it a potential candidate for the next generation eEDM experiment. Our study also reveals that it has a large scalar-pseudoscalar (S-PS) P, T-violating interaction constant, W-s = 284.2 kHz. To judge the accuracy of the obtained results, we have calculated parallel and perpendicular magnetic hyperfine structure (HFS) constants and compared with the available experimental values. The results of our calculation are found to be in nice agreement with the experimental values. Therefore, by looking at the HFS results, we can say that both E-eff and W-s values are also very accurate. Further, We have derived the relationship between these quantities and the ratio which will help to get model independent value of eEDM and S-PS interaction constant. (C) 2016 AIP Publishing LLC.

Auger decay rates of core hole states using equation of motion coupled cluster method - Ghosh, Aryya; Vaval, Nayana; Pal, Sourav (Chemical Physics, 2017)
The recent development of Linac coherent light source high intense X-ray laser makes it possible to create double core ionization in the molecule. The generation of double core hole state and its decay is identified by Auger spectroscopy. The decay of this double core hole (DCH) states can be used as a powerful spectroscopic tool in chemical analysis. In the present work, we have implemented a promising approach, known as CAP-EOMCC method, which is a combination of complex absorbing potential (CAP) and equation -of-motion coupled cluster (EOMCC) approach to calculate the lifetime of single and double core hole states. We have applied this method to calculate the lifetime of the single core hole (K-LL) and double core hole (KK-KLL) states of CH4, NH3 and HF molecules. The predicted lifetime is found to be extremely short. (C) 2016 Elsevier B.V. All rights reserved.

Correlation trends in the magnetic hyperfine structure of atoms: a relativistic coupled-cluster case study - Talukdar, Kaushik; Sasmal, Sudip; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Physical Review A, 2018)
The role of electron correlation in the hyperfine structure of alkali metals and alkaline earth metal monopositive ions in their ground electronic configuration is investigated using the Z-vector method in a relativistic coupled-cluster regime within the singles and doubles approximation. The systematic effects of core-correlating functions, polarization of core electrons, and high-lying virtual functions on core electrons correlation are studied. The study reveals that the core-correlating function plays a significant role in core polarization and thus is very important for precise calculation of the wave function near the nuclear region. The inner-core electrons (1s-2p) require very high virtual energy functions for proper correlation. Therefore, the all-electron correlation treatment and the inclusion of higher-energy virtual functions are the key factors for precise calculation of the hyperfine structure constant of atoms. Our calculated values are in excellent agreement with the available experimental values, which also implies that the wave function produced by the Z-vector method is accurate enough for further calculation of the parity- and time-reversal symmetry-violating properties in atoms and molecules.

Lower scaling approximation to EOM-CCSD: a critical assessment of the ionization problem - Dutta, Achintya Kumar; Vaval, Nayana; Pal, Sourav (International Journal of Quantum Chemistry, 2018)
In this article, we investigate the performance of different approximate variants of the EOM-CCSD method for calculation of ionization potential (IP), as compared to EOM-CCSDT reference values. None of the lower scaling approximations to the EOM-CCSD method give a consistent performance for valence, inner valence, and core ionization, favoring one, or the other depending on the nature of the approximation used. The parent EOMIP-CCSD method gives superior performance for valence IP but can show large errors for inner valence and core ionization. The problem is particularly severe for core-ionization, where even the EOMIP-CCSDT method cannot provide quantitative accuracy.
Keywords: EOM-CCSD; Ionization potential; lower scaling

Nuclear parity- and time-reversal-symmetry violation in the (HgH)-Hg-201 molecule - Talukdar, Kaushik; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Physical Review A, 2019)
Investigation of the nuclear magnetic quadrupole moment (MQM) is an excellent way to reveal the new physics in the hadron sector of matter. Therefore, we investigate the violation of parity (P) and time-reversal (T) invariance induced by the MQM of the( 201) Hg nucleus in the HgH molecule, which has been proposed as a very promising candidate for the experimental search of the electric dipole moment of electron [M. G. Kozlov and A. Derevianko, Phys. Rev. Lett. 97, 063001 (2006)]. We report the precise value of the molecular parameter, W-M, associated with the P, T-odd nuclear MQM-electron interaction in (HgH)-Hg-201 using the four-component relativistic coupled-cluster method. This parameter is required to interpret the experimental P, T-odd frequency shift in terms of the MQM of nuclei. Furthermore, the magnetic hyperfine structure (HFS) constants of the molecule are computed at the same level of theory. We also study the role of core-correlating functions and the virtual energy functions in the calculations of the HFS constant and W-M. The most reliable value of W(M )in HgH is obtained as 3.22 x 10 (33) Hz/e cm (2) with an uncertainty of around 6%.

Relativistic coupled-cluster investigation of parity (P) and time-reversal (T) symmetry violations in HgF - Talukdar, Kaushik; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2019)
We employ the Z-vector method in the four-component relativistic coupled-cluster framework to calculate the parity (P) and time-reversal (T) symmetry violating scalar-pseudoscalar nucleus-electron interaction constant (W-s), the effective electric field (E-eff) experienced by the unpaired electron, and the nuclear magnetic quadrupole moment-electron interaction constant (W-M) in the open-shell ground electronic state of HgF. The molecular frame dipole moment and the magnetic hyperfine structure (HFS) constant of the molecule are also calculated at the same level of theory. The outcome of our study is that HgF has a high value of E-eff (115.9 GV/cm), W-s (266.4 kHz), and W-M (3.59 x 10(33) Hz/e cm(2)), which shows that it can be a possible candidate for the search of new physics beyond the standard model. Our results are in good agreement with the available literature values. Furthermore, we investigate the effect of the basis set and the virtual energy functions on the computed properties. The role of the high-energy virtual spinors is found to be significant in the calculation of the HFS constant and the P,T-odd interaction coefficients. Published under license by AIP Publishing.

Electronic structure parameter of nuclear magnetic quadrupole moment interaction in metal monofluorides - Talukdar, Kaushik; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2020)
The electronic structure parameter (W-M) of the nuclear magnetic quadrupole moment (MQM) interaction in numerous open-shell metal monofluorides (viz., MgF, CaF, SrF, BaF, RaF, and PbF) is computed in the fully relativistic coupled-cluster framework. The electron-correlation effects are found to be very important for the precise calculation of W-M in the studied molecular systems. The molecular MQM interaction parameter scales nearly as Z(2) in the alkaline earth metal monofluorides, where Z is the nuclear charge of metal. Our study identifies (RaF)-Ra-223 as a good candidate for the experimental search of the nuclear MQM, which can help unravel the physics beyond the standard model in the hadron sector of matter.

Negative ion resonance states: the fock-space coupled-cluster way - Basumallick, Suhita; Sajeev, Y.; Pal, Sourav; Vaval, Nayana (Journal of Physical Chemistry A, 2020)
The negative ion resonance states, which are electron-molecule metastable compound states, play the most important role in free-electron controlled molecular reactions and low-energy free-electron-induced DNA damage. Their electronic structure is often only poorly described but crucial to an understanding of their reaction dynamics. One of the most important challenges to current electronic structure theory is the computation of negative ion resonance states. As a major step forward, coupled-cluster theories, which are well-known for their ability to produce the best approximate bound state electronic eigen solutions, are upgraded to offer the most accurate and effective approximations for negative ion resonance states. The existing Fock-space coupled-cluster (FSCC) and the equation-of-motion coupled-cluster (EOM-CC) approaches that compute bound states are redesigned for the direct and simultaneous determination of both the kinetic energy of the free electron at which the electron-molecule compound states are resonantly formed and the corresponding autodetachment decay rate of the electron from the metastable compound state. This Feature Article reviews the computation of negative ion resonances using the FSCC approach and, in passing, provides the highlights of the equivalent EOM-CC approach.

Relativistic coupled-cluster study of BaF in search of CP violation - Talukdar, Kaushik; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Journal of Physics B-Atomic Molecular and Optical Physics, 2020)
BaF is one of the potential candidates for the experimental search of the electric dipole moment of the electron (eEDM). The NL-eEDM collaboration is building a new experimental set up to measure the eEDM using the BaF molecule (The NL-eEDM collaboration, 2018 Eur. Phys. J. D 72: 197). To analyze the results of such an experiment, one would require the accurate value of the molecular P, T-odd interaction parameters that cannot be measured from any experiment. In this work, we report the precise value of the P, T-odd interaction parameters of the BaF molecule obtained from the four-component relativistic coupled-cluster calculations. We also calculate the hyperfine structure (HFS) constants of the same molecule to assess the reliability of the reported molecular parameters. The calculated HFS constants show good agreement with the available experimental values. Further, the systematic effects of electron-correlation along with the roles of inner-core electrons and the virtual energy functions in the calculation of the studied properties of BaF are investigated.
Keywords: electric dipole moment of the electron; electron-correlation; Relativistic effects

Role of electron correlation in the P, T-odd effects of CdH: a relativistic coupled-cluster investigation - Talukdar, Kaushik; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Physical Review A, 2020)
We investigate the parity (P) and time-reversal (T) symmetry violating effects in the CdH molecule and perform the relativistic coupled-cluster calculation of the molecular parameters-E-eff, W-s, and W-M-related to the electric dipole moment of electron (eEDM) interaction, the scalar-pseudoscalar (S-PS) nucleus-electron neutral current coupling, and the nuclear magnetic quadrupole moment (MQM) interaction with electrons, respectively. We also compute the molecular dipole moment and the magnetic hyperfine structure coupling constant of CdH. The values of E-eff, W-s, and W-M obtained by us in the said molecule are 12.2 GV/cm, 14.0 kHz, and 0.82 x 10(33) Hz/e cm(2), respectively, within an uncertainty of 10%. Furthermore, we study the trend of electron-correlation in the computed properties of CdH and that of the P, T-odd parameters in the group-12 monohydrides (i.e., ZnH, CdH, and HgH).

Shape resonance of sulphur dioxide anion excited states using the CAP-CIP-FSMRCCSD method - Basumallick, Suhita; Bhattacharya, Sumantra; Jana, Irina; Vaval, Nayana; Pal, Sourav (Molecular Physics, 2020)
We have studied the shape resonance of excited states of sulphur dioxide (SO2) anion by using the correlated independent particle Fock space multi-reference coupled cluster (CAP-CIP-FSMRCCSD) method augmented by complex absorption potential. These resonant states have been trapped experimentally in recent years by electron collision. In particular, we have investigated e(-)-SO2 scattering and computed the negative-ion resonance states of the anion responsible for the two resonances around 4.45 and 6.56 eV and compared the results with the existing experimental observations. From the computational results using the CAP-CIP-FSMRCCSD method, it has been observed that both the resonances near 4.45 and 6.56 eV result from A(1) symmetries. [GRAPHICS] .
Keywords: CAP augmented correlated independent particle (CAP-CIP-FSMRCCSD); complex absorption potential (CAP); coupled cluster; Fock space multireference coupled cluster (FSMRCCSD); shape resonance

Interatomic Coulombic decay in Neon-Helium cluster: a complex absorbing potential based equation-of-motion coupled cluster investigation - Ghosh, Aryya; Pal, Sourav; Vaval, Nayana (Molecular Physics, 2021)
The interatomic Coulombic decay (ICD) of the Ne(2s(-1)) and Ne(2s(-1)2p(-1)) states in neon-helium dimer is studied using highly accurate complex absorbing potential based equation-of-motion coupled cluster (CAP-EOMCC) method. The ICD decay process for the Ne(2s(-1)) state in neon-helium dimer is closed at its equilibrium bond distance. However, the decay channel is open at large bond distance of 6.2 angstrom. The decay channel for the double ionised Ne(2s(-1)2p(-1)) state is open at 3.46 angstrom. From our calculations, we have noticed that the decay rate of Ne(2s(-1)2p(-1)) state in neon-helium dimer is four times faster compared to the Ne(2s(-1)) state. We have also investigated how the decay rate of Ne(2s(-1)) state in neon-helium cluster varies in the presence of different helium environment. [GRAPHICS] .
Keywords: double ionised state; equation-of-motion coupled cluster (EOMCC); He droplet; interatomic Coulombic decay (ICD)

Resonance study: effect of partial triples excitation using complex absorbing potential-based Fock-space multi-reference coupled cluster - Jana, Irina; Basumallick, Suhita; Pal, Sourav; Vaval, Nayana (International Journal of Quantum Chemistry, 2021)
Resonances are metastable states with finite lifetime. They play important role in physics, chemistry and biology. The theoretical calculation of resonance state is a challenging problem. In this paper we have studied the shape resonance of Be, Mg, N-2 and CO. We have used correlated independent particle approximation to the Fock space multi-reference coupled cluster singles-doubles with third-order triples (CAP-CIP-FSMRCCSD(T)) method augmented by complex absorption potential. The resonance energy and decay widths are obtained by solving a non-Hermitian eigen-value problem within FSMRCC framework. The effects of the lowest order triples on the resonance energy and decay are studied.
Keywords: complex absorbing potential; electron affinity; Fock‐ negative ion resonance; partial triples; space MRCC

Decay processes in cationic alkali metals in microsolvated clusters: a complex absorbing potential based equation-of-motion coupled cluster investigation - Kumar, Ravi; Ghosh, Aryya; Vaval, Nayana (Journal of Chemical Theory and Computation, 2022)
We have employed the highly accurate complex absorbing potential based ionization potential equation-of-motion coupled cluster singles and doubles (CAP-IP-EOM-CCSD) method to study the various intermolecular decay processes in ionized metals (Li+, Na+, K+) microsolvated by water molecules. For the Li atom, the electron is ionized from the 1s subshell. However, for Na and K atoms, the electron is ionized from 2s and both 2s and 2p subshells, respectively. We have investigated decay processes for the Li+-(H2O)(n) (n = 1-3) systems, as well as Na+-(H2O)(n) (n = 1, 2), and K+-H2O. The lithium cation in water can decay only via electron transfer mediated decay (ETMD) as there are no valence electrons in lithium. We have investigated how the various decay processes change in the presence of different alkali metal atoms and how the increasing number of water molecules play a significant role in the decay of microsolvated systems. To see the effect of the environment, we have studied Li+-NH3 in comparison to Li+-H2O. In the case of Na+-H2O, we have studied the impact of bond distance on the decay width. The effect of polarization on decay width was checked for the X+-H2O (X = Li, Na) systems. We used the PCM model to study the polarization effect. We have compared our results with existing theoretical and experimental results wherever available in the literature.

Effect of charge and solvation shell on non-radiative decay processes in s-block cationic metal ion water clusters - Kumar, Ravi; Ghosh, Aryya; Vaval, Nayana (Journal of Chemical Physics, 2023)
Intermolecular Coulombic decay or electron transfer-mediated decay are the autoionization processes through which a molecule can relax. This relaxation is only possible if the inner valence's ionization potential (IP) exceeds the system's double ionization potential (DIP). To study the effects of charge and solvation shell, we have calculated the IP, DIP values, and lifetime of Na-2s and Mg-2s temporary bound states in various optimized structures of Na+-(H2O)(n) and Mg2+-(H2O)(n) (n = 1-5) micro-solvated clusters, where n water molecules are distributed in a way that some are directly bound to the metal ion and the rest to the water molecules. The first and second solvation shells are the names for the former and the latter water-binding positions, respectively. For a given n, the lifetime of decaying states is longer when water molecules are in the second solvation shell. We found that the Mg-2p state can decay for all n values in Mg2+-(H2O)(n) clusters, whereas the Na-2p state's decay is possible for n >= 2 in Na+-(H2O)(n) clusters. Our findings highlight the influence of metal ions' charge, different solvation shell structures, and the number of water molecules on the decay rate. These systems are relevant to the human body, which makes this study significant.

Insights into adsorption of various gases on extra-framework cations of zeolite: a dispersion corrected DFT study on zeolite cluster models with Li plus , Na plus and K plus ions - Devasia, George; Kumar, Ravi; Vaval, Nayana; Krishnamurty, Sailaja (Microporous and Mesoporous Materials, 2023)
Design of an economical and sustainable gas separation material is relevant in several industrial processes. Zeolites with tunable pore sizes are ideal molecular sieves of many gases. The adsorption centers of these molecular sieves are extra-framework Lewis acid centers. In this study, we attempt to delineate the electronic properties of such centers (Li+, Na+ and K+) and their sorption properties towards N2, O2, CO, CO2 and H2. Negative framework of zeolites are modeled using different cluster models that present distinct electronic environment and role of this environment on the Lewis acidity of the cation. The sorption property towards different gases is evaluated using dispersion corrected DFT studies. The results obtained are benchmarked for one of the studied model using CCSD calculations. The results indicate that while the local environment modulates the adsorption properties, the relative adsorption properties between different ions follow the same order irrespective of the type of negative framework modeled. This reveals that intrinsic atomic properties of the charge compensating cations drive the sorption properties of the zeolites. Adsorption energies compounded with the analysis of IR stretching frequencies of the adsorbed gases reveals that Li centers shows molecular adsorption (charge donation to the cationic centers) towards N2 as compared to O2 and towards CO2/CO as compared to H2, demonstrating the applicability of Li-Zeolites as ideal membranes for oxygen concentrators and syngas separation. These adsorption studies are ratified by the BOMD simulations at 300 K, where H2 and O2 desorbs while N2, CO and CO2 remains adsorbed to the cationic site.
Keywords: BOMD simulation; CO/CO2/H2 separation; Extra-framework cation; N2/O2 separation; zeolites

Relativistic coupled-cluster study of SrF for low-energy precision tests of fundamental physics - Talukdar, Kaushik; Buragohain, Haimyapriya; Nayak, Malaya K. K.; Vaval, Nayana; Pal, Sourav (Theoretical Chemistry Accounts, 2023)
SrF, being a laser-coolable molecule, can be an interesting system for spectroscopic tests of fundamental physics. We present an electronic structure study of this molecule within the four-component relativistic coupled-cluster singles and doubles (RCCSD) framework and employ the RCCSD-based methods to compute its molecular-frame dipole moment and core properties such as hyperfine structure coupling constant and molecular P, T-odd electronic structure parameters that are of great importance for the high-precision tests of fundamental physics. The impact of basis set size, Hamiltonian and nuclear model on the property calculation of SrF is also investigated. The computed results are in good agreement with the available experimental values. The present study shows that the SrF molecule could be useful for high-precision molecular experiments to explore physics beyond the Standard Model of elementary particles.
Keywords: Coupled cluster theory; CP violation; Hyperfine structure; Molecular spectroscopy; Relativistic effects

Relaxation of the 2a1 ionized water dimer: an interplay of intermolecular Coulombic decay (ICD) and proton transfer processes - Kumar, Ravi; Ghosh, Aryya; Vaval, Nayana (Journal of Chemical Physics, 2024)
This article investigates the relaxation dynamics of the ionized 2a(1) state of a water molecule within a water dimer. The study was motivated by findings from two previous pieces of research that focused on the relaxation behaviors of the inner-valence ionized water dimer. The present study discloses an observation indicating that water dimers display specific fragmentation patterns following inner-valence ionization, depending on the position of the vacancy. Vacancies were created in the 2a(1) state of the proton-donating water molecule (PDWM) and proton-accepting water molecule (PAWM). Utilizing Born-Oppenheimer molecular dynamics simulations, the propagation of the 2a(1) ionized state was carried out for both scenarios. The results revealed proton transfer occurred when the vacancy resided in the PDWM, accompanied by the closing of decay channels for O-H bond distance (RO-H) > 1.187 & Aring; (matching Richter et al.'s findings). Conversely, when vacancy was on PAWM, we observed no closing of decay channels (aligning with Jahnke et al.'s findings). This difference translates to distinct fragmentation pathways. In PDWM cases, 2a(1) state ionization leads to H3O+ -OH center dot formation. In contrast, PAWM vacancies result in decay pathways leading to H2O+-H(2)O(+ )products.

Synthesized novel chromogenic reagent and sensor: detection and identification of dichlorvos - Gedam, Ashwin D.; Katiya, Manish M.; Dhonde, Madhukar G.; Ganorkar, Kapil S.; Thakare, Vijay J.; Mandlik, Prashant R.; Jadhao, Nitin L.; Gajbhiye, Jayant M.; Kumar, Ravi; Vaval, Nayana (Heliyon, 2024)
We developed a novel chromogenic reagent and sensor by selective approach, for the detection and identification of dichlorvos, which we tested with the thin layer chromatography method. For the first time, we reported in situ-generated glyoxal as a hydrolysis product, which then interacts with isoniazid to produce a yellow-colored cyclic compound. We used well-known spectroscopic techniques to confirm the chemical identity of the final product. We initially investigated the reaction using a variety of approaches, followed by attempts to establish the reaction mechanism using Density Functional Theory by Gaussian software.
Keywords: DFT analysis; Dichlorvos; Gloyxal; Hydrazone; Isoniazid

Charge transfer effect on relaxation mechanism in hydrated pyrrole-water systems following N-2s ionization - Kumar, Ravi; Bhattacharjee, Kankana; Ghosh, Aryya; Vaval, Nayana (ChemPhysChem, 2025)
This study investigates the relaxation mechanisms of pyrrole and pyrrole-water clusters (C4H5N-(H2O)n, where n=0-3 \${n = 0 - 3}\$ ) following N-2s ionization of pyrrole. Using various theoretical methods, we focus on the influence of water molecules and charge transfer on these non-radiative relaxation pathways. Our simulations included pyrrole solvated in 494 explicit water molecules equilibrated at 300 K and also employed a polarizable continuum model (PCM) to make the system more realistic and gain additional insights. In hydrated environments, the hydrogen bonding network between pyrrole and surrounding water molecules facilitates enhanced non-radiative relaxation pathways following inner valence ionization. Since these are hydrogen bonding systems, we have explored the possibility of proton transfer, which could occur in conjunction with other electronic decay processes.
Keywords: ab initio-calculations; auger decay; charge transfer; proton transfer; pyrrole

Relativistic extended-coupled-cluster calculations of P , T -odd sensitivity parameters for diatomic molecules - Talukdar, Kaushik; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2025)
We demonstrate the first application of the four-component relativistic extended-coupled-cluster (ECC) method, a variational approach, to determine the P , T -odd molecular electronic structure parameters necessary for high-precision spectroscopic measurements on ultracold molecules. We calculate the P , T -odd sensitivity parameters for two moderately heavy, laser-coolable diatomic molecules (SrH and SrF), as well as two relatively lighter open-shell molecules (CaH and CaF) in their ground electronic state, 2 Sigma 1/2. The hyperfine structure constants of 87Sr in the SrF and SrH molecules are also computed and compared with available experimental results to assess the accuracy of our calculations. Furthermore, we examine the roles of electron correlation, relativity, basis set, and virtual spinors in ECC calculations of the sensitivity parameters. Our study reveals that the ECC method is a reliable technique for studying P , T -odd properties of diatomic molecules such as CaH, CaF, SrH and SrF, yielding results in very good agreement with those obtained using two widely employed analytic approaches: the Z-vector technique and the linear expectation-value method within the relativistic single-reference coupled-cluster singles and doubles framework.

Solvent and pH effects on the ionization energies of bio-organic molecules: a case study of alanine and glycine - Kumar, Ravi; Ghosh, Aryya; Vaval, Nayana (Physical Chemistry Chemical Physics, 2026)
The ionization energies (IEs) and double ionization energies (DIEs) of the amino acids alanine and glycine have been studied in the gas phase and a polarizable continuum model (PCM) to account for solvent effects. Amino acids undergo structural modifications, particularly in their functional groups, in response to changes in their chemical environment, such as pH. Four possible different structural forms, neutral (NH2-R-COOH), zwitterionic (NH3+-R-COO-), deprotonated (NH2-R-COO-), and protonated (NH3+-R-COOH), were generated for each amino acid. In this study, we use these four forms to explore the effects of protonation and deprotonation (pH effect) on the IEs of inner-valence states. In amino acids, IEs and DIEs are essential for evaluating the energetic viability of inner-valence-initiated non-radiative decay processes, such as interatomic Coulombic decay (ICD). All IE and DIE values were calculated using the complete active space perturbation theory (CASPT2) method. A comparison is made across gas-phase and PCM environments to assess the impact of solvation. The observed variations in IE and DIE values indicate a lot about alanine and glycine's electronic structure and chemical reactivity under different physiological and environmental conditions (pH effect and solvation), hence improving our understanding of their functional roles in biochemical systems.